The Relationship Between Speed And Agility Towards The Ability To Dribble The Ball In Football Games Of Students At Inpres 12/79 Gattareng Elementary School - Yoyo Prianto; Alif Aryadi Hardi; Khalid Rijaluddin (STAMINA, 2026)
This study aims to determine the relationship between speed and agility towards dribbling skills in football games for students of Inpres 12/79 Gattareng Elementary School. The type used in this study is correlation research. The population in this study were 124 students of Inpres 12/79 Gattareng Elementary School. The sample in this study was 30 students using a purposive sampling technique. This research instrument used a 30-meter running test, Agility T-test, and dribbling test. Data analysis used statistical analysis with the help of a computer through the SPSS program. The results of the study showed that there was a significant relationship between speed and dribbling ability with a sig value of 0.005, there was a significant relationship between agility and dribbling ability with a sig value of 0.009, and there was a significant relationship between speed and agility together with dribbling ability with a sig value of 0.011. Keywords: Speed; Agility; Dribble; Football.